Is the Area of Apum-Damascus Mentioned in the Mari Archives? - Pitard, Wayne T. (Bulletin of ASOR, 1986)
In 1939 Dossin published a list of several kings and states mentioned in the Mari letters as having economic dealings with Mari. Among the kings in the list were two rulers of a land of Apum. While Dossin assumed that these kings lived in the land of Apum located in northern Mesopotamia, W. F. Albright in 1941 proposed that they were rulers of the land of Apum in southern Syria, around the area of Damascus. Albright's proposal has been widely accepted among biblical scholars and historical geographers. However, recently-published Mari letters indicate that the kings listed by Dossin belong to the Mesopotamian Apum rather than the Damascene one. There are, in fact, no known references to the Damascene Apum in the Mari letters.